2003
DOI: 10.1038/sj.onc.1206762
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of aquaporins in colorectal carcinogenesis

Abstract: Aquaporins (AQPs) are important in controlling water permeability. As AQP1 is known as a serum-responsive gene, we hypothesized that AQP expression may be involved in the development of human cancer. By reverse transcriptase-polymerase chain reaction analysis, expression of AQPs 1, 3, and 5 was found in seven colon and colorectal cancer cell lines. Western blot analysis confirmed their expression in four of these cell lines. In situ hybridization demonstrated that during colorectal carcinogenesis, the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
157
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 180 publications
(169 citation statements)
references
References 23 publications
11
157
0
1
Order By: Relevance
“…Expression of hAQP1 is frequently associated with brain tumors, colon cancers, and microvessels of multiple myeloma (MM) paralleling angiogenesis [6][7][8]. Other reports have alluded to the role of other AQPs in the development of human cancer [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of hAQP1 is frequently associated with brain tumors, colon cancers, and microvessels of multiple myeloma (MM) paralleling angiogenesis [6][7][8]. Other reports have alluded to the role of other AQPs in the development of human cancer [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, expression of AQP3 was increased in renal cell cancer, as was AQP5 in pancreatic cancer [9,10]. AQP1 appears to be involved in cell cycle control [8,11], and expression of hAQP1, hAQP3, and hAQP5 have been shown to be simultaneously induced during lymphocyte activation [12]. Most recently, based on the novel oncogenic properties of AQP1, increased levels of AQP1 were suggested to play a role in tumorigenesis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing the literature, we find that this association has been suggested mainly in relation to a role for these proteins in cell volume changes, 3,5,8 or in the case of a subgroup of AQPs, called aquaglyceroporins, 11,12 to their permeability to solutes such as glycerol and hydrogen peroxide. [13][14][15][16][17][18] Additionally, various studies have demonstrated that AQP expression is modified over the course of the cell cycle [19][20][21][22][23] and, more recently, we have shown that overexpression of AQP1 and AQP3 alters the levels of essential checkpoint proteins (cyclins) relevant for cell cycle progression, in addition to modifying the levels of transcription factors, and cytokines.…”
Section: Introductionmentioning
confidence: 83%
“…[2][3][4][5] Since the beginning, the idea behind a role for AQPs in tumor process was basically associated with their contribution to changes in cell volume necessary for cells to proliferate and differentiate. Initial studies demonstrated high AQP1 expression in proliferating microvessels of many tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Th e aquaporins (AQPs), integral membrane proteins, have been shown to be expressed in multiple epithelial and endothelial transporting fl uids (Verkman 2005) as well as tumor cells (Moon et al 2003;Hu and Verkman 2006). In in vitro and in vivo, AQPs can also facilitate tumor cell migration across the blood vessels (Hu and Verkman 2006).…”
Section: Th E Eff Ect Of C Longa and Curcumin On The Female Reproducmentioning
confidence: 99%